Larval description of Limnephilus barbagaensis Malicky, Sekhi & Lounaci 2019 (Trichoptera: Limnephilidae), a micro-endemic of Algeria, with notes on its ecology - Karaouzas, Ioannis; Dambri, Besma (Zootaxa, 2022)
The hitherto unknown larva of Limnephilus barbagaensis Malicky, Sekhi & Lounaci 2019, micro-endemic of the Aures Mountains (Mounts des Aures, Algeria), is described. The diagnostic features of the species are listed, illustrated, compared with those of similar species, and some information on the ecology is included. In addition, the first record of Hydropsyche siltalai Döhler 1963 in the Aures Region and Northeast Algeria is also reported.